Evaluation of Oxidative Stress, Antioxidant Capacity, Thiol/Disulfide Homeostasis, and HO-1 Levels in Neonates with Cyanotic Congenital Heart Disease: A Prospective Case-Control Study - Kurt, Abdullah; Tayman, Cüneyt; Çakır, Ufuk; Koyuncu, İsmail (American Journal of Perinatology, 2025)
Oxidative stress is a major contributor to the pathogenesis of cyanotic congenital heart disease (CCHD), yet data in neonates are limited. This study aimed to assess oxidative stress markers, thiol/disulfide homeostasis, and heme oxygenase-1 (HO-1) levels in neonates with CCHD.A prospective case-control study was conducted, including 62 term neonates with CCHD and 63 healthy controls. Serum levels of total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), native and total thiol, disulfide (SS), and HO-1 were measured within 72 hours of birth. Thiol/disulfide ratios were calculated. Survival-based subgroup and receiver operating characteristic (ROC) analyses were performed.CCHD neonates had significantly decreased TAS, elevated TOS and OSI levels, and reduced HO-1, native thiol, and total thiol levels compared with controls (p < 0.001). Disulfide/native thiol and disulfide/total thiol ratios were significantly increased, while the native thiol/total thiol ratio was decreased (p < 0.05), indicating oxidative imbalance. Among nonsurvivors, lower HO-1 and thiol levels and higher oxidative stress markers were observed, though not all reached statistical significance (p > 0.05). ROC analysis showed that TOS (cut-off > 12.96; sensitivity 96.83%) and OSI (cut-off > 0.86; specificity 86.96%) were strong predictors.HO-1 and oxidative stress parameters showed excellent diagnostic accuracy (OSI [area under the curve (AUC): 0.942], TOS [AUC: 0.927], TAS [AUC: 0.904], HO-1 [AUC: 0.859]).Neonates with CCHD exhibit significant oxidative stress and impaired antioxidant defense early in life. Suppressed HO-1 expression and disturbed thiol/disulfide balance suggest increased vulnerability to oxidative injury. These biomarkers may serve as early indicators for clinical risk stratification and could guide antioxidant-based therapeutic strategies.
Keywords: congenital heart disease; oxidative stress; antioxidant capacity; thiol/disulfide homeostasis; hemoxygenase-1; neonates